FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN KEHAMILAN (K1) BERDASARKAN UMUR, PENDIDIKAN DAN SOSIAL BUDAYA - Hermina Humune (Akademi Kebidanan Griya Husada Surabaya, 2017)
K1 visit is the first time a mother visits during pregnancy. K1 is divided into pure K1 and K1 access. Pure K1 is the contact of first-time pregnant women with health workers in the 1st trimester. K1 access is the first contact of pregnant women with health workers instead of the 1st trimester (more than 12 weeks' gestation). Prenatal care should be done before 12 weeks' gestation. At BPS Enny pregnancy check has reached the target (95%), but in 2014-2016 the average number of K1 accesses (53.76%) was higher than pure K1 (46.33%). This study aims to describe the K1 visit based on age, education and socio-culture at BPS Enny Surabaya for the period June-July 2017. Method: This study is descriptive. The population is all pregnant women who check in BPS Enny for the period June-July 2017. The sampling is done on a non probability sampling with accidental sampling technique. The sample size is 50 people, data is obtained from primary and secondary data, and the results are processed in frequency tables and cross tabulations. The results of the study describe the majority of visits were K1 access as much as 54%. The majority of pregnant women who carry out pure K1 are aged 20-35 years as many as 12 people (60%), have secondary education as many as 11 people (61.11%) and social culture that supports health as many as 12 people (52.17%), while pregnant women the majority of those who conducted K1 access were <20 years old as many as 11 people (64.71%), low educated as many as 13 people (65%), and social culture that did not support health as many as 16 people (59.26%). Discussion: Based on the research, it can be concluded that in BPS Enny, there are still many pregnant women who do K1. Therefore, we as health workers are able to provide information to WUS who are getting married about the importance of early pregnancy examinations at least before 12 weeks' gestation.